Linking Transformational Leadership and Work Environment Towards Employee Engagement - Pringgabayu, Dematria; Satiadharma, Moehamad (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
This study was to determine the impact of transformational leadership and work environment on employee engagement at Bidlabfor Polda with organizational normative commitment as an intervening variable. The research method used in this study is a quantitative research method with primary data sources used in this study. The subjects in this study included employees of the Forensic Laboratory of the Java Regional Police, a total of 53 people. The sample was collected using census sampling technique, which is a sampling technique that takes into account all available populations for sampling. For data analysis methods, descriptive analysis and partial least squares (PLS) analysis were used. Based on data analysis on the impact of transformational leadership style and work environment on employee performance at Bidlabfor Polda with organizational normative commitment as the mediating variable, it can be concluded that commitment of the organization is the variable that has the greatest influence in forming an optimal environment. employee contract. Therefore, transformational leadership can only shape employee engagement if it is associated with good normative engagement with the organization.